The Cavendon luck - Bradford, Barbara Taylor, 1933- (Bradford, Barbara Taylor, 1933- Cavendon chronicles., 2016)
"From the #1 New York Times bestselling author comes a captivating epic saga of courage and honor, following the aristocratic Inghams and the loyal Swann family who have served them for centuries. It is 1938 in England, and Miles and Cecily Ingham have lead the family in bringing the Cavendon estate back from the brink of disaster. But now, with the arrival of World War II, Cavendon Hall will face its biggest challenge yet. It is a challenge that will push the Inghams and Swanns to protect each other and the villagers, and reveal their true capacity for survival and rebirth. Told with Bradford's deft, evocative prose and featuring a beloved cast of characters, Cavendon Luck is a story of intrigue, romance, sorrow, and joy that readers won't soon forget"--